Engaging in cyber hygiene: the role of thoughtful decision-making and informational interventions - Howell, Christian; Maimon, David; Muniz, Caitlyn; Kamar, Eden; Berenblum, Tamar (Frontiers in Psychology, 2024)
Introduction The effectiveness of human-centric cybersecurity largely depends on end-users’ adherence to security and privacy behaviors. Understanding and predicting variations in the adoption of these safeguards is crucial for both theoretical advancement and practical application. While existing frameworks are often adapted from health science literature, there is potential to enhance these models by incorporating criminological constructs relevant to online victimization. This study introduce rational choice theory of thoughtfully reflective decision-making (TRDM) into the information security domain. TRDM suggests that variations in cognitive decision-making capabilities influence behavioral outcomes, particularly in the context of security and privacy practices. Methods The study employed a field experiment to test the applicability of TRDM in predicting end-users’ engagement in security and privacy behaviors. Participants were exposed to security-related warnings, with the hypothesis that thoughtfully reflective decision-makers would be more likely to adopt robust protective behaviors. Data was collected on participants’ responses to these security warnings, as well as their overall adherence to privacy and security practices. Results The findings support the theoretical framework: individuals exhibiting thoughtfully reflective decision-making tendencies demonstrated a higher likelihood of engaging in privacy and security behaviors. Specifically, participants with higher TRDM scores were more likely to adopt protective behaviors when warned of the consequences of non-compliance. These results indicate that cognitive decision-making capabilities significantly influence the likelihood of engaging in cybersecurity practices. Discussion The study challenges the prevailing one-size-fits-all approach to cybersecurity by highlighting the importance of individual differences in cognitive decision-making. Thoughtfully reflective decision-makers are better equipped to adopt preventive security measures, suggesting the need for more tailored interventions in cybersecurity education and risk assessment. This research contributes to the development of sophisticated risk assessment tools aimed at mitigating vulnerabilities and reducing users’ susceptibility to digital threats. Incorporating TRDM into information security models provides a more nuanced understanding of user behavior, offering insights into how cognitive processes influence cybersecurity adherence.